2019
DOI: 10.2174/1574888x13666180912125157
|View full text |Cite
|
Sign up to set email alerts
|

CellSaic, A Cell Aggregate-Like Technology Using Recombinant Peptide Pieces for MSC Transplantation

Abstract: In the field of stem cell therapy, research on the application of mesenchymal stem cells (MSCs) has flourished because of the various functions. On the other hand, research on the method of cell transplantation has developed from the administration of cell suspensions to cell-sheet engineering and 3D technology. In the trend, a cell transplantation platform named CellSaic, which is a combination of xeno-free recombinant scaffolds in a cell aggregate-like shape, was developed. CellSaic is the cell transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The advantage of μ -pieces, such as human recombinant peptide petaloid, was reported for islet cell culture and cell transplantation [ 41 ]. Spheroid-like cell aggregation-formed combination cells with μ -pieces can prevent central necrosis within cell aggregates, because nutrients and waste products can pass through the inner spheroid [ 42 ]. Our results showed that IPC generated from canine AT-MSCs in the 3D culture system showed better DTZ staining and insulin secretion compared with cells in conventional 2D culture dishes.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of μ -pieces, such as human recombinant peptide petaloid, was reported for islet cell culture and cell transplantation [ 41 ]. Spheroid-like cell aggregation-formed combination cells with μ -pieces can prevent central necrosis within cell aggregates, because nutrients and waste products can pass through the inner spheroid [ 42 ]. Our results showed that IPC generated from canine AT-MSCs in the 3D culture system showed better DTZ staining and insulin secretion compared with cells in conventional 2D culture dishes.…”
Section: Discussionmentioning
confidence: 99%
“…Here we developed a 3D culture system with a RCP petaloid μ-piece to successfully generate effective IPCs that marked 65.6% of cell expansion rate (according to DNA quantity, data not shown) and reasonable SI value. Moreover, this RCP petaloid μ-piece is xeno-antigen free and is provided as clinical grade 22,23 . Our established two-step generation protocol is thus a xeno-antigen-free protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The CellSaic maintains cell viability in vivo when transplanted with target cells. Additionally, CellSaic is xeno-antigen free and clinical grade has been achieved 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the focus of this study is on the ADSCs as a new cell source of MSCs 68 and the establishment of a new 2-step protocol for the differentiation of IPCs from ADSCs with a short culture duration and functional efficiency 9 . Moreover, this 2-step protocol was modified into a xeno-antigen free and three-dimensional (3D) culture protocol 10,11 which improved cell quality and function in vitro / in vivo and resulted in the normalization of diabetic nude mice blood glucose over 120 days 12 . In other words, this modified protocol is reaching the pre-clinical level of proof of a concept.…”
Section: Introductionmentioning
confidence: 99%